Technology and techniques in automotive film production - Maltcev, Ilia (2018)
In this work I review technologies which are used in automotive films, such as carcommercials or action chase scenes. In the theoretical part I describe different camerasystems and platforms as well as their placement and movement for producing dynamicshots that emotionally impact audience. Additionally, I introduce a brief historical evolution ofsuch systems. Furthermore, I examine vehicle coordination and various driving techniquesthat improve visual imagery. These findings are applied in the practical part, where I producea demo reel which contains my own car shots.